Lithium and Copper Induce the Osteogenesis-Angiogenesis Coupling of Bone Marrow Mesenchymal Stem Cells via Crosstalk between Canonical Wnt and HIF-1α Signaling Pathways - Zhen Tan; Baochun Zhou; Jianrui Zheng; Yongcan Huang; Hui Zeng; Lixiang Xue; Deli Wang (Hindawi Limited, 2021)
The combination of osteogenesis and angiogenesis dual-delivery trace element-carrying bioactive scaffolds and stem cells is a promising method for bone regeneration and repair. Canonical Wnt and HIF-1α signaling pathways are vital for BMSCs' osteogenic differentiation and secretion of osteogenic factors, respectively. Simultaneously, lithium (Li) and copper (Cu) can activate the canonical Wnt and HIF-1α signaling pathway, respectively. Moreover, emerging evidence has shown that the canonical Wnt and HIF signaling pathways are related to coupling osteogenesis and angiogenesis. However, it is still unclear whether the lithium- and copper-doped bioactive scaffold can induce the coupling of the osteogenesis and angiogenesis in BMSCs and the underlying mechanism. So, we fabricated a lithium- (Li+-) and copper- (Cu2+-) doped organic/inorganic (Li 2.5-Cu 1.0-HA/Col) scaffold to evaluate the coupling osteogenesis and angiogenesis effects of lithium and copper on BMSCs and further explore its mechanism. We investigated that the sustained release of lithium and copper from the Li 2.5-Cu 1.0-HA/Col scaffold could couple the osteogenesis- and angiogenesis-related factor secretion in BMSCs seeding on it. Moreover, our results showed that 500 μM Li+ could activate the canonical Wnt signaling pathway and rescue the XAV-939 inhibition on it. In addition, we demonstrated that the 25 μM Cu2+ was similar to 1% oxygen environment in terms of the effectiveness of activating the HIF-1α signaling pathway. More importantly, the combination stimuli of Li+ and Cu2+ could couple the osteogenesis and angiogenesis process and further upregulate the osteogenesis- and angiogenesis-related gene expression via crosstalk between the canonical Wnt and HIF-1α signaling pathway. In conclusion, this study revealed that lithium and copper could crosstalk between the canonical Wnt and HIF-1α signaling pathways to couple the osteogenesis and angiogenesis in BMSCs when they are sustainably released from the Li-Cu-HA/Col scaffold.